Students’ self-regulation, critical thinking, and learning performance in learning e-commerce through facebook - Jacquelin S. Linggu; Zaidatun Tasir (International Journal of Education and Learning, 2022)
This study aims to analyse the effect of Facebook as a social learning environment in relation to students’ self-regulation (SR), critical thinking (CT) and learning performance in an e-Commerce course. A total of 295 undergraduate students taking the course were selected using cluster random sampling to identify their SR and CT. 50 out of 295 students were then selected purposively and were involved in the intervention process of e-Commerce course learning using Facebook. The post-test result indicated that SR, CT and learning performance in e-Commerce learning had improved after they went through the intervention process. Meanwhile, a positive correlation could be seen between CT and learning performance only, when analysed using Pearson correlation. Furthermore, a cross-tabulation analysis revealed a positive relationship pattern between the students’ SR, CT and learning performance. Hence, this suggests that academic performance can be improved through SR and CT.